Chosen Keywords in the Discourse of British Politicians on Brexit: A Pragmatic Analysis - Kubicha, Patrycja (Respectus Philologicus, 2022)
The aim of the article was to select and analyze keywords concerning central Brexit-related themes found in chosen speeches delivered in the years 2013–2021 by politicians from three British parties: the Conservative Party, the Labour Party, and the Brexit Party. The decision regarding Brexit had been made as a result of the referendum in which a slight majority of British citizens had voted for the United Kingdom of Great Britain and Northern Ireland to leave the EU. Via a pragmatic analysis conducted with the help of the program AntConc on a sample of one hundred transcripts of chosen speeches from sources such as the official UK government website and media websites, two keywords that played a crucial role in the discourse on Brexit were chosen, namely leave and remain. They appeared in the speeches of members of all three parties mentioned above. In their rhetorical and persuasive speeches delivered before the referendum, the politicians tried to convince the British society to support Brexit or be against it. In their speeches given after the referendum, they accented, e.g., that the decision made by the majority of the voters needs to be honoured.